Susceptibility quantitative trait loci for pathogenic leucocytosis in SCG/Kj mice, a spontaneously occurring crescentic glomerulonephritis and vasculitis model. (July 2014) - Hamano, Y.; Abe, M.; Matsuoka, S.; Zhang, D.; Kondo, Y.; Kagami, Y.; Ishigami, A.; Maruyama, N.; Tsuruta, Y.; Yumura, W.; Suzuki, K.
Summary The spontaneous crescentic glomerulonephritis‐forming/Kinjoh (SCG/Kj) mouse, a model of human crescentic glomerulonephritis (CrGN) and systemic vasculitis, is characterized by the production of myeloperoxidase‐specific anti‐neutrophil cytoplasmic autoantibody (MPO‐ANCA) and marked leucocytosis. This study was performed to identify the specific populations of leucocytes associated with CrGN and susceptibility loci for pathogenic leucocytosis. Four hundred and twenty female (C57BL/6 × SCG/Kj) F2 intercross mice were subjected to serial flow cytometry examination of the peripheral blood (PB). Kidney granulocytes and monocytes were examined histopathologically. Linkage analyses were performed with 109 polymorphic microsatellite markers. Correlation studies revealed that increase of the granulocytes, F4/80+ cells, CD3+CD4−CD8− T cells and dendritic cells (DCs) in peripheral blood (PB) were associated significantly with glomerulonephritis, crescent formation and vasculitis. In kidney sections, F4/80low cells were observed in crescent, while F4/80high cells were around the Bowman's capsules and in the interstitium. Numbers of F4/80+ cells in crescents correlated significantly with F4/80+ cell numbers in PB, but not with numbers of F4/80+ cells in the interstitium. Genome‐wide quantitative trait locus (QTL) mapping revealed three SCG/Kj‐derived non‐Fas QTLs for leucocytosis, two on chromosome 1 and one on chromosome 17. QTLs on chromosome 1 affected DCs, granulocytes and F4/80+ cells, but QTL on chromosome 17 affected DCs and granulocytes. We found CrGN‐associated leucocytes and susceptibility QTLs with their positional candidate genes. F4/80+ cells in crescents are considered as recruited inflammatory macrophages. The results provide information for leucocytes to be targeted and genetic elements in CrGN and vasculitis.